2023
DOI: 10.1111/ijfs.16434
|View full text |Cite
|
Sign up to set email alerts
|

The effects of free radicals and metal ion on milk protein β‐lactoglobulin (BLG) glyco‐oxidation

Abstract: In this study, the effects of H 2 O 2 , 2,2 0 -Azobis(2-amidinopropane) dihydrochloride (AAPH) and metal ion Fe 3+ on β-lactoglobulin (BLG) glyco-oxidation were investigated. The results demonstrated all the three inducers caused BLG morphology change and higher molecular weight BLG-glucose (BLG-Glu) adducts formation. H 2 O 2 and AAPH significantly accelerated BLG oxidation by increasing carbonyl content and decreasing freesulphydryls (P < 0.05). However, Fe 3+ showed little influence on carbonyl and free sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The maximum FI of the control group was 188.16 (at an emission wavelength of 358.4 nm), whereas the samples sterilized under 60 • C-20 min, 60 • C-35 min, and 65 • C-40 min conditions showed a maximum FI of 173.97 (360.8 nm), 167.95 (361 nm), and 164.41 (361.2 nm), respectively. It can be seen that the maximum FI of LFM shifted to the long-wave direction after LTLT, and the FI decreased significantly with the increase in the pasteurization intensity as compared to the control group, which may be due to the fact that the hydrolyzed glucose and galactose combined with partially unhydrolyzed lactose and protein shielded the tryptophan, exposing the tryptophan residues to the hydrophilic environment [47,48], which indicated that some small molecules of fluorescence substances were generated at the end of the MR and that the LTLT facilitated the MR. As shown in Figure 10b, the maximum FI of LFM reached 165.37 (359 nm), 160.81 (360.8 nm), and 159.97 (359.4 nm) after pasteurization at 70 °C-15 s, 80 °C-30 s, and 90 °C-30 s conditions, respectively. The FI of LFM after HTST was lower than that of the control group, and the FI decreased with the increase in the pasteurization intensity, and the wavelengths of its maximum FI ranged from 359 to 360.8 nm; therefore, the HTST is beneficial to the MR, which is consistent with the results of the LTLT.…”
Section: Color Change During Storage At 37 • Cmentioning
confidence: 95%
“…The maximum FI of the control group was 188.16 (at an emission wavelength of 358.4 nm), whereas the samples sterilized under 60 • C-20 min, 60 • C-35 min, and 65 • C-40 min conditions showed a maximum FI of 173.97 (360.8 nm), 167.95 (361 nm), and 164.41 (361.2 nm), respectively. It can be seen that the maximum FI of LFM shifted to the long-wave direction after LTLT, and the FI decreased significantly with the increase in the pasteurization intensity as compared to the control group, which may be due to the fact that the hydrolyzed glucose and galactose combined with partially unhydrolyzed lactose and protein shielded the tryptophan, exposing the tryptophan residues to the hydrophilic environment [47,48], which indicated that some small molecules of fluorescence substances were generated at the end of the MR and that the LTLT facilitated the MR. As shown in Figure 10b, the maximum FI of LFM reached 165.37 (359 nm), 160.81 (360.8 nm), and 159.97 (359.4 nm) after pasteurization at 70 °C-15 s, 80 °C-30 s, and 90 °C-30 s conditions, respectively. The FI of LFM after HTST was lower than that of the control group, and the FI decreased with the increase in the pasteurization intensity, and the wavelengths of its maximum FI ranged from 359 to 360.8 nm; therefore, the HTST is beneficial to the MR, which is consistent with the results of the LTLT.…”
Section: Color Change During Storage At 37 • Cmentioning
confidence: 95%